THE EFFECT OF PARENTAL INVOLVEMENT IN CHILDRENâS READING MOTIVATION IN INDONESIA - ERIZAR, ERIZAR (P3M STAIN Parepare, 2015)
Many researchers have presented about the need of parental involvement in childrenâs learning which is positively related to achievement. The more parents involvement in childrenâs learning especially in reading, the more benefcial are the achievement effects. Also, Programs which involve parents in reading with their children, supporting their work on homework assignments, or tutoring them using materials and instructions provided by teachers, show particularly impressive results. Although, there are some obstacles faced by parents in getting involved in their childrenâs reading activity, they will be able to solve by applying some ideas which are suggested. The research also show that the earlier in a childâs educational process parent involvement begins, the more powerful the effects will be. Early childhood education programs with strong parent involvement components have amply demonstrated the effectiveness of this approach